The effectiveness of the filial service in KPPN Alor - M. N. B. C. Neolaka; Ajis Salim Adangdjaha; Yulius Soleman Ferdinan Padama (Goodwood Publishing, 2020)
Abstract Purpose: This research aims to to measure the effectiveness of the filial service in KPPN Alor which has been operating for 8 years. Measurement of the effectiveness was conducted by following two approaches: the attainment goals and the strategic constituent approaches.. Research methodology: This research is a type of case study with a qualitative approach. Research informants are KPPN Kupang employees and KPPN Filial Alor stakeholders. Measurement of effectiveness was done by approaching the achievement of objectives and strategic constituency approaches. Data were collected through observation, interviews and documentation. The analysis of data followed pattern matching techniques, while the validity of data was tested by conducting data triangulation. Results: The results showed that the Filial Service of KPPN Alor was not effective by the attainment goal and the strategic constituent approach. There were many aspects that influenced the ineffectiveness of the Filial Service: the regulation, the policy, the quality of human resources, the service quality, and the use of information technology. Limitations: This study measured the effectiveness of Filial Service with two approaches namely the attainment goals and the strategic constituent approaches. Contribution: The benefits of this study are theoretically to develop the effectiveness of measurements and practically to improve and refine the filial service policy and similar policies. Keywords: KPPN filial, The effectiveness of measurements, Public service, The treasury service